Enhancing Problem-Solving Skills in Mathematics: Applying LDMAT and SRL for Students with Learning Difficulties - Heru Kurniawan; Nila Kurniasih; Dita Yuzianah (Jurnal Gantang, 2023)
This study examines the effectiveness of the LDMAT and SRL models in improving problem-solving skills in students with learning difficulties in mathematics. The research involved 18 junior high school students and employed a mixed research design. The assessment of problem-solving skills was conducted through pre-test and post-test measurements, consisting of 10 essay-based tests and weekly assignments. Furthermore, problem-solving understanding was assessed based on the strategies utilized by students in the post-test. Data analysis involved using paired t-tests to compare pre-test and post-test results. The findings indicate that applying the LDMAT and SRL models significantly enhanced problem-solving skills in students with learning difficulties in mathematics, particularly among female students. Moreover, the students exhibited an improved understanding of problem-solving procedures. This study underscores the efficacy of the LDMAT and SRL models in enhancing problem-solving abilities and promoting deeper comprehension of problem-solving strategies among students with learning difficulties in mathematics.